Những câu hỏi liên quan
TV
Xem chi tiết
PH
Xem chi tiết
NM
Xem chi tiết
LT
Xem chi tiết
H24
30 tháng 12 2018 lúc 10:08

\(\frac{x+4}{2000}+\frac{x+3}{2001}=\frac{x+2}{2002}+\frac{x+1}{2003}\)

\(\Leftrightarrow\frac{x+2004}{2000}+\frac{x+2004}{2001}=\frac{x+2004}{2002}+\frac{x+2004}{2003}\)

\(\Leftrightarrow\left(x+2004\right)\left(\frac{1}{2000}+\frac{1}{2001}-\frac{1}{2002}-\frac{1}{2003}\right)\)

Dễ thấy: \(\left(\frac{1}{2000}+\frac{1}{2001}-\frac{1}{2002}-\frac{1}{2003}\right)\ne0\Rightarrow x+2004=0\Leftrightarrow x=-2014\)

Bình luận (0)
NV
30 tháng 12 2018 lúc 10:38

x = -2014

ti-ck nha

.........

Bình luận (0)
KS
30 tháng 12 2018 lúc 11:43

\(\frac{x+1}{10}+\frac{x+1}{11}+\frac{x+1}{12}=\frac{x+1}{13}+\frac{x+1}{14}\)

\(\frac{x+1}{10}+\frac{x+1}{11}+\frac{x+1}{12}-\frac{x+1}{13}-\frac{x+1}{14}=0\)

\(\left(\frac{1}{10}+\frac{1}{11}+\frac{1}{12}-\frac{1}{13}-\frac{1}{14}\right)\left(x+1\right)=0\)

\(\Rightarrow x+1=0\left(\frac{1}{10}+\frac{1}{11}+\frac{1}{12}-\frac{1}{13}-\frac{1}{14}\ne0\right)\)

\(x=-1\)

Vậy \(x=-1\)

Bình luận (0)
NT
Xem chi tiết
MT
11 tháng 6 2019 lúc 15:19

em ko bieets hu hu

Bình luận (0)
H24
11 tháng 6 2019 lúc 15:41

#)Giải :

a) \(A=\left(\frac{\sqrt{x}}{2}-\frac{1}{2\sqrt{x}}\right)\left(\frac{x\sqrt{x}}{\sqrt{x}-1}-\frac{x+\sqrt{x}}{\sqrt{x}-1}\right)\)

\(=\frac{x-1}{2\sqrt{x}}\left(\frac{\sqrt{x}\left(\sqrt{x}-1\right)^2-\sqrt{x}\left(\sqrt{x}+1\right)^2}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}\right)\)

\(=\frac{x-1}{2\sqrt{x}}.\frac{x\sqrt{x}-2x+\sqrt{x}-x\sqrt{x}-2x-\sqrt{x}}{x-1}\)

\(=\frac{-4}{2\sqrt{x}}=-2\sqrt{x}\)

Bình luận (0)
H24
11 tháng 6 2019 lúc 15:44

#)Giải :

b) Để \(A>-6\Leftrightarrow-2\sqrt{x}>-6\)

\(\Leftrightarrow\sqrt{x}< 3\)

\(\Leftrightarrow x< 9\)

Kết hợp với đkxđ => 0 < x < 9

Bình luận (0)
VD
Xem chi tiết
NU
7 tháng 9 2018 lúc 20:12

\(\frac{x-1}{4}=\frac{2x+1}{5}\)

\(\Rightarrow5\left(x-1\right)=4\left(2x+1\right)\)

\(\Rightarrow5x-5=8x+4\)

\(\Rightarrow5x-8x=4+5\)

\(\Rightarrow-3x=9\)

\(\Rightarrow x=-3\)

vậy_

\(\frac{x+2}{x-1}=\frac{x-3}{x+1}\)

\(\Rightarrow\left(x+2\right)\left(x+1\right)=\left(x-1\right)\left(x-3\right)\)

\(\Rightarrow x^2+x+2x+2=x^2-3x-x+3\)

\(\Rightarrow x^2+x+2x-x^2+3x+x=3-2\)

\(\Rightarrow7x=1\)

\(\Rightarrow x=\frac{1}{7}\)

vậy_

Bình luận (0)
NM
Xem chi tiết
NM
Xem chi tiết
H24
Xem chi tiết